2002
DOI: 10.1002/ecja.10055
|View full text |Cite
|
Sign up to set email alerts
|

Subband signal processing adaptive array with a data transmission scheme inserting a cyclic prefix

Abstract: SUMMARYThe advantages of subband signal processing adaptive array (SBAA) are the ability to perform parallel signal processing in each subband division and the substantial reduction in the total computational load. However, the price is not preventing a drop in performance, for example, the incorporation of delayed waves, and a countermeasure must be found. Therefore, in this paper, we propose introducing a scheme that inserts a guard interval (cyclic prefix), which is commonly adopted in Orthogonal Frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For adaptive array operation, we have confirmed that single-carrier transmission with cyclic prefix, and frequency-domain block signal processing, which is called subband signal processing, is a promising way [21]- [23]. Based on this background, subband adaptive array for spacetime block coding (STBC) in single carrier MIMO transmission with cyclic prefix has been proposed [24].…”
Section: Mimo For Broadband Systemsmentioning
confidence: 88%
“…For adaptive array operation, we have confirmed that single-carrier transmission with cyclic prefix, and frequency-domain block signal processing, which is called subband signal processing, is a promising way [21]- [23]. Based on this background, subband adaptive array for spacetime block coding (STBC) in single carrier MIMO transmission with cyclic prefix has been proposed [24].…”
Section: Mimo For Broadband Systemsmentioning
confidence: 88%
“…This figure shows the proposed schemes almost converge within two blocks, and particularly for SNR ≥ 10dB, one block is tolerable. Here we should remark that conventional subband adaptive algorithm [10] requires the pilot signals of at least N r blocks, and under the above condition, the correlation matrix becomes singular.…”
Section: Computer Simulationsmentioning
confidence: 98%
“…Figure 2 shows the structure of the SBAA considered in this study. It is known the addition of cyclic prefix (CP) which is widely used in OFDM (orthogonal frequency division multiplex) to the transmit data is effective also in single carrier case using subband processing in the receiver [9], [10]. In this study, the addition of sufficient length of CP (equal to max…”
Section: Mrc Sbaamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CORPS, three conventional AAs, TDLAA, SBAA, and SBAA with cyclic prefix (SBAA-CP) [10] are considered for the comparison.…”
Section: Performance Evaluationmentioning
confidence: 99%